Reduction of Intensive Care Unit Length of Stay: The Case of Early Mobilization. Issue 3 (July 2020) - Hunter, Alex; Johnson, Leslie; Coustasse, Alberto
Abstract : Bed rest or immobilization is frequently part of treatment for patients in the intensive care unit (ICU) with critical illness. The average ICU length of stay (LOS) is 3.3 days, and for every day spent in an ICU bed, the average patient spends an additional 1.5 days in a non-ICU bed. The purpose of this research study was to analyze the effects of early mobilization for patients in the ICU to determine if it has an impact on the LOS, cost of care, and medical complications. The methodology for this study was a literature review. Five electronic databases were used, with a total of 26 articles referenced for this research. Early mobilization suggested a decrease in delirium by 2 days, reduced risk of readmission or death, and reduced ventilator-assisted pneumonia, central line, and catheter infections. Length of stay in the ICU was reduced with statistical significance in several studies examining early mobilization. Limited research on cost of ICU LOS indicated potential savings with early mobilization. When implementing early mobilization in the ICU, total costs were decreased and medical complications were reduced. Early mobilization should become a standard of care for critically ill but stable patients in the ICU.